Numerical and experimental investigation of early stage diesel sprays. (1st July 2016) - Ghiji, M.; Goldsworthy, L.; Brandner, P.A.; Garaniya, V.; Hield, P.
Highlights: We investigate in- and near-nozzle spray dynamics for a single hole diesel injector. We analyze the morphology of the jet at early and quasi-steady stages of injection. A laser-based backlit imaging technique is used for analysis of spray structures. An Eulerian/Large-eddy simulation approach is employed for numerical analysis. The effects of grid resolution and numerical scheme were discussed. Abstract: Experimental and numerical investigations of primary atomization in a high-pressure diesel jet are presented. Information on flow processes and structures inside and near nozzle exit are described at early and quasi-steady stages of injection. The numerical method is based on the Volume Of Fluid (VOF) phase-fraction interface capturing technique, in an Eulerian framework. The influence of grid resolution, convection interpolation scheme and temporal integration scheme on the modeling of jet physics are investigated. The present flow setup includes in-nozzle disturbances with the no-slip condition at the walls. All experimental operating conditions are replicated in the numerical models. The early stage liquid jet leading edge demonstrates an umbrella-shaped structure in the numerical results which is in qualitative agreement with experimental imaging. Data obtained provide insight into the flow behavior in the dense region including commencement of fragmentation and early spray angle formation. Experimental images show a cloud of air–fuel mixture at the early stage of injection. The existence of ingested air inside the injector after needle closure could be the source of the observed deviation between experimental and numerical results. The results show that the jet breakup rate and liquid core length increase in cases with higher grid resolutions. The early spray angle from the numerical results at the quasi-steady stage, shows good agreement with experimental data.